Application of brain oscillations in neuropsychiatric diseases: selected papers from "Brain Oscillations in Cognitive Impairment and Neurotransmitters" Conference held on April 29th - May 1st 2011 at Istanbul Kultur University in Istanbul, Turkey - Başar-Eroglû, E. (Clinical neurophysiology, 2013)
Neurophysiological techniques in the study of the excitability, connectivity, and plasticity of the human brain / P.M. Rossini and F. Ferreri -- Brain's alpha, beta, gamma, delta, and theta oscillations in neuropsychiatric diseases: proposal for biomarker strategies / E. Bașar, C. Bașar-Eroğlu, B. Güntekin and G.G. Yener -- Preferred pre-stimulus EEG states affect cognitive event-related potentials / R.J. Barry -- The in vivo topography of cortical changes in healthy aging and prodromal Alzheimer's disease / A. Prestia [and 8 others] -- The value of spontaneous EEG oscillations in distinguishing patients in vegetative and minimally conscious states -- A.A. Fingelkurts, A.A. Fingelkurts, S. Bagnato, C. Boccagni and G. Galardi -- The auditory steady-state response (ASSR): a translational biomarker for schizophrenia / B.F. O'Donnell [and 5 others] -- Clinical relevance of animal models of schizophrenia / M. Koch -- Auditory-evoked alpha oscillations imply reduced anterior and increased posterior amplitudes in schizophrenia / C. Bașar-Eroğlu, C. Schmiedt-Fehr and B. Mathes -- Early auditory gamma band response abnormalities in first hospitalized schizophrenia / G.W. Taylor, R.W. McCarley and D.F. Salisbury -- Early auditory gamma-band responses in patients at clinical high risk for schizophrenia / V.B. Perez [and 6 others] -- Converging evidence for gamma synchrony deficits in schizophrenia / B.J. Roach, J.M. Ford, R.E. Hoffman and D.H. Mathalon -- Connectivity and local activity within the fronto-posterior brain network in schizophrenia / A. Sharma, M. Weisbrod and S. Bender -- Neurophysiological findings in patients with bipolar disorder / T. Onitsuka, N. Oribe and S. Kanba -- Brain oscillations in bipolar disorder in search of new biomarkers / A. Özerdem, B. Güntekin, M.I. Atagün and E. Bașar -- Resting state cortical EEG rhythms in Alzheimer's disease: towards EEG markers for clinical applications: a review / F. Vecchio [and 7 others] -- Biomarkers in Alzheimer's disease with a special emphasis on event-related oscillatory responses / G.G. Yener and E. Bașar -- Resting state brain oscillations and symptom profiles in attention deficit/hyperactivity disorder / R.J. Barry and A.R. Clarke -- Event-related oscillations reflect functional asymmetry in children with attention deficit/hyperactivity disorder / J. Yordanova, V. Kolev and A. Rothenberger -- Review of delta, theta, alpha, beta, and gamma response oscillations in neuropsychiatric disorders -- E. Bașar and B. Güntekin -- Brain oscillations as biomarkers in neuropsychiatric disorders: following an interactive panel discussion and synopsis / G.G. Yener and E. Bașar.